Implementasi Microsoft Power Bi Untuk Dashboard Visualisasi Data Akademik Mahasiswa Fakultas Teknik Universitas Janabadra - Jemmy Edwin Bororing; Amrullah Pasadi (Informasi Interaktif, 2022)
Janabadra University is one of the campuses that as a lot of information from various fields, this university has 4 faculties, namely, the Faculty of Economics and Business, the Faculty of Law, the Faculty of Engineering and the Faculty of Agriculture. The Janabadra University portal has some information, namely, PMB (new student admissions), student portal, lecturer portal and alumni portal. Each of these portals has data and information that will continue to grow every year. In particular, the student portal contains various identity and academic data for Janabadra University students. The purpose of this study is to build a dashboard in the academic field that provides important information that is useful for monitoring student studies and as information supporting decision making. The method used in the construction of the dashboard is the Business Intelligence Roadmap. The Business Intelligence Roadmap is a guide for developing BI decision support applications using structured data. This method has 6 phases, namely justification, which is to identify existing problems, planning is to identify data needs, business analysis is to determine the information to be displayed on the dashboard, design is to design the data warehouse and determine the application used, constraction is to build a data warehose by using NDS + DDS architecture and dashboard development using Power BI applications, and deployment by testing the dashboard. This study builds 3 dashboards, namely student profile dashboards based on identity, student profile dashboards based on academics and student study dashboards using the average GPA as a reference